Kānčhatkān kō̜ngthun kap rabop sukkhaphāp chumchon (Samnakngān Wičhai læ Phatthanā Rabop Sukkhaphāp Chumchon, Sathāban Phatthanā Sukkhaphāp ʻĀsīan, Mahāwitthayālai Mahidon, 2012)
On self-management of community-contributed fund for community health care service, case studies at Bangrakam Sub-district Administrative Organization, Nakhon Pathom Province, at Nongsarai Sub-district Administartive Organization, Kanchanaburi Province, Central Thailand, and at Sithan Sub-district Adminsitrative Organization, Yasothon Province, Northeastern Thailand; proceedings of the 6th forum on participatory action for the development of community-based health care service system in Thailand.